SUPPLY CHAIN MANAGEMENT FOR GREEN HYDROGEN PRODUCTION AT PT. XYZ - Intan Kusumadewi; Rivaldi Maulana Anwar (Jurnal Mekanika dan Manufaktur, 2026)
This study analyzed Supply Chain Management (SCM) for green hydrogen production at PT. XYZ. The development of green hydrogen requires an integrated and resilient supply chain covering upstream resource provision, production (electrolysis), purification and storage, and downstream distribution to end users. A qualitative-descriptive method was used with literature review and desk research as primary data sources. The SCOR (Plan, Source, Make, Deliver, Return) model was employed to map and evaluate each stage of the hydrogen supply chain. Findings indicated that geothermal- based electricity provides a reliable baseload advantage for continuous electrolysis, enabling stable production. Critical constraints were identified in water treatment, electrolyzer and compressor reliability, storage capacity, and distribution infrastructure. Coordination between divisions and digital monitoring were observed as key enablers for operational stability. Based on the SCOR mapping, recommendations include optimizing electrolyzer efficiency, investing in advanced storage technologies, strengthening inter- departmental integration with unified data platforms, and expanding distribution modes (tube trailers, pipelines, HRS). This research provides a baseline overview for PT. XYZ and supports strategic planning for scalable green hydrogen deployment in Indonesia.